A hopane triterpenoid from the mycelium of Isaria japonica in Vietnam - Tuan, Nguyen Ngoc; Kim Anh, Tran Thi; Kuo, Ping-Chung; Wu, Tian-Shung; Thang, Tran Dinh (Vietnam Journal of Science and Technology, 2017)
A hopane triterpenoid (11b, 22-dihydroxyhopane) was isolated from the methanol extract of the mycelium of Isaria japonica in Vietnam. The structure of this compound was elucidated using a combination of 1D and 2D NMR techniques (1H-, 13C-NMR, COSY, HSQC and HMBC). In the study, we reported the comprehensive 1H- and 13C-NMR spectral data of 11b, 22-dihydroxyhopane for the first time.